Analisis Komparatif Konsep Mahar menurut Mazhab Imam Syafi’i dengan Praktik Sosial Budaya di Desa Taduasa Kabupaten Buton Selatan - La Emrin; Lajusu Lajusu; La Jidi (JURNAL ILMIAH PENDIDIKAN KEBUDAYAAN DAN AGAMA, 2026)
D Dowry (mahar) is an obligation of a groom to his bride in Islamic marriage, symbolizing respect and responsibility. In the Buton community, mahar also develops as a customary tradition known as boka, which carries both symbolic and socio-cultural meanings. This study aims to analyze the concept of mahar according to the Shafi’i school of law and its implementation in Taduasa Village, South Buton Regency. This research uses a qualitative method with data collection techniques including interviews, documentation, and literature review. The findings show that mahar is viewed as a symbol of respect for women and is determined based on lineage and social status. According to the Shafi’i school, such practices are permissible as long as they are based on mutual agreement and do not burden the groom. However, excessively high dowry amounts in some cases may hinder marriage. This study concludes that the mahar tradition in Taduasa Village remains consistent with Shafi’i principles but should be adjusted to the Islamic values of ease and public welfare.